(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the ideas and views of the development of society in the rashhas of the mystics from Fakhruddin Ali Safi’s work “Rashahotu aynil-hayot”. The rashhas of the representatives of the Khojagon line mainly express their views on building a peaceful, patriot and enlightened society.